Kajian Ikonografis Bahasa Rupa Uang Kertas Indonesia Masa Revolusi - Baskoro Suryo Banindro (Institut Seni Indonesia Yogyakarta, 2012)
Bank note as a medium for visual communication, in it loaded with aesthetic values associatedwith beauty problems. Composed of letters, pictures, colors and unique printing techniques. Paper moneyas a sign of payment, in addition to having intrinsic value in the form of nominal value, has also thefunction of signification, that is a function where bookmarks (signifier), which is concrete as a medium ofexchange, laden with abstract concepts or meanings commonly referred to as marker (signified) in formof text and images. In the image of paper money, which is poured visual expression can reflect ideas,concepts or symbolic meanings related to hegemony, legitimacy, ideology, the existence, sovereignty ofboth states and rulers.Oeang Repoeblik Indonesia (ORI), is the first legitimate currency owned by the Republic ofIndonesia after independence. Since printed in December 1945 to December 1949, in addition topictorial inzet Sukarno, the Indonesian tradition of cultural objects more dominate and become the mainimage. Departure from this phenomenon, need to be studied in greater depth and comprehensive visualand symbolic aspects of paper money during the ORI physical revolution. By looking at the artifacts of theimages on paper money ORI 1945 - 1949, built on the revolutionary period, besides the symboliclanguage of art is a form of symbolic expression to foster community spirit of nationalism and patriotismof the newly independent Indonesia, as well as communicating, showing identity, reflecting the spirit andthe factual circumstances of his time.